Nos fuimos quedando en silencio. La agonía del Chile de la transición. Daniel Mansuy, Instituto de estudios de la sociedad, Santiago de Chile, 2016. (ISBN: 978-956-8639-28-3) - Hoevel, Carlos (2016)
Fil: Hoevel, Carlos. Pontificia Universidad Católica Argentina; Argentina